2010
DOI: 10.1016/j.compscitech.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titanium on copper–titanium/carbon nanofibre composite materials

Abstract: Copper/carbon nanofibre composites containing titanium varying from 0.3wt% to 5wt% were made, and their thermal conductivities measured using the laser flash technique. The measured thermal conductivities were much lower than predicted. The difference between measured and predicted values has often been attributed to limited heat flow across the interface. A study has been made of the composite microstructure using x-ray diffraction, transmission electron microscopy and Raman spectroscopy. It is shown in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In the case of sintering of the Ti 25 Cu 75 ribbons in contact with graphite, no evidence of diffusion of carbon through layers of the alloy was detected. This result is in agreement with observations reported by Lloyd et al [31], who obtained Cu–Ti/carbon fiber composites by hot pressing Cu-coated nanofibers mixed with a Ti powder and found TiC layers covering some carbon fibers. The transport of titanium to carbon was by means of diffusion of the former through the copper layers.…”
Section: Resultssupporting
confidence: 93%
“…In the case of sintering of the Ti 25 Cu 75 ribbons in contact with graphite, no evidence of diffusion of carbon through layers of the alloy was detected. This result is in agreement with observations reported by Lloyd et al [31], who obtained Cu–Ti/carbon fiber composites by hot pressing Cu-coated nanofibers mixed with a Ti powder and found TiC layers covering some carbon fibers. The transport of titanium to carbon was by means of diffusion of the former through the copper layers.…”
Section: Resultssupporting
confidence: 93%
“…It is reported that the basal plane TC of natural GF is over 1000 Wm À1 ÁK À1 , which is about two orders of magnitude higher than the c direction (perpendicular to the basal plane of GF). 23 Therefore, in order to obtain high TC, it is necessary to fabricate composites in which the GFs orientate preferably. The GF/copper composites with the volume fraction of GF ranging from 20% to 70% were fabricated by the optimal process, i.e.…”
Section: Composite Microstructurementioning
confidence: 99%
“…In a CNX reinforced composite it has to be ensured that there are still CNXs present in the final composite. When bringing CNXs together with a matrix metal under high temperatures/pressures, this might also result in a modification, amorphisation or complete degradation of the CNX material [37], especially when additives are involved in a surface modification process. …”
Section: Conclusion and Remarksmentioning
confidence: 99%